Teaching Ability of Economic Teachers with Certification and its Impact on Students’ Economic Achievement - Salmiah Salmiah; Yulia Novita; Alfiah Alfiah; Novian Aldo (STAI Hubbulwathan Duri, 2022)
The objective of the research was to know the impact of teaching ability of economic teachers that were certified upon the student’s achievement in economic subject. The type of this research was quantitative method. The population and sample of the research were all economics students with total of forty-four students. The data of teaching ability was collected by questionnaires and student’s achievement were taken from documentation of economic scores from economic teachers.Then, the data was analyzed with serial correlation. Based on the result of data analysis, it could be concluded that there was a positive relationship of teaching ability of economics teachers that werecertified with students’ achievement in economic subject with very low relationship.